The effect of implementing physical activity patterns on physical fitness and motor skills in students aged 10–12 years - Ma'arif, Ilmul; Setyawan, Risfandi (Bima Loka: Journal of Physical Education, 2025)
The emergence of a problem where the fitness and motor skills of students indicate the need for a patterned activity that describes a play activity tailored to their characteristics. The purpose of this study is to determine the application of a physical activity pattern model on the physical fitness and motor skills of students aged 10-12 years. The method used a quantitative descriptive approach with a pre-experimental design (one group pretest posttest design). Sampling was conducted using purposive sampling, with 110 students aged 10-12 years old participating. The research instruments used were the TKJI for ages 10-12 years for physical fitness tests and motor skills tests with TGMD-2 (locomotor and object control abilities), and difference analysis with a paired t-test. The results of the paired sample t-test showed that the effect size (Cohen's d) for fitness was 1.50 (very large) and for motor skills was 1.13 (large). In addition, the r-effect value calculated from the t-value showed a result of r = 0.83 for fitness and r = 0.75 for motor skills. There was a 15.2% increase in fitness and a 16.4% increase in motor skills, indicating that the physical activity pattern had a positive impact on students' fitness and motor skills. In conclusion, there is a significant effect of physical activity patterns on students' physical fitness and motor skills. Recommendations for future researchers conducting similar studies include adding a control group and additional variables. Due to the limitations of using a pre-experimental design in this study, which did not use a control group or assign tasks randomly, the causal inference is not strong.